(3TQM ahGFO GdTjN CMeOs - (3GdUbQj, GdeWjQaj, GdGMSGFj, GdHMQGfj, YeGO GdOjf, CMeO Hf Rjf GdOjf Hf EHQGgje Hf UbQ, J (B1241(3g`s ((3eMeO bdj Hf ejQRG GdNhFjfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CeG HYO ajbhd GdYHO GdeScjf CMeO Hf Rjf GdOjf GdCMSGFj Ef LfGH GdeObb(B... (3bO GdJeS efj EKHGJ HYV GdcdeGJ(B...s
(3BNQgG (B:s
(3QCjJ GdebGUO HYjOI ef JfGhd GdCagGe(B... (3Edi gfG GfJgi TQM gPg GdahGFOs
(3jdjg cJGH(B: (3eSCdI aj GNJdGa CbhGd GdYdeGA aj HbGA CLSGO GdCfHjGA aj bHhQges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B129s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B185s
(3GdCYdGe(B: (3L(B1(3, U(B129s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds